2007
DOI: 10.1007/s10689-007-9131-2
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of cancer genetics services: The Royal Marsden telephone clinic model

Abstract: We have conducted a telelink telephone-led cancer genetic counselling model at The Royal Marsden NHS Foundation Trust. The study commenced in March 2004 and evaluation of the clinic was conducted over 17 months from March 2005 to the end of July 2006. A total of 612 patients had telephone consultations during this time, 228 of whom were referred from primary care with a median of 30 patients counselled per month (range of 19-63, depending on staff availability with average of two staff per clinic). Waiting tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…This particular confusion stresses the need for clear definition and language when discussing SDM, which has been attempted in a prior publication from this group (Cohen et al 2012). We suspect that the use of telephone GC as a primary SDM may be lower than reported here, however recent literature is demonstrating increased use and acceptance of telephone genetic counseling (Bradbury et al 2011;Doughty Rice et al 2010;Graves et al 2010;Shanley et al 2007;Sutphen et al 2010).…”
Section: Discussionmentioning
confidence: 69%
“…This particular confusion stresses the need for clear definition and language when discussing SDM, which has been attempted in a prior publication from this group (Cohen et al 2012). We suspect that the use of telephone GC as a primary SDM may be lower than reported here, however recent literature is demonstrating increased use and acceptance of telephone genetic counseling (Bradbury et al 2011;Doughty Rice et al 2010;Graves et al 2010;Shanley et al 2007;Sutphen et al 2010).…”
Section: Discussionmentioning
confidence: 69%
“…While we have demonstrated a viable DVD-based model, other models are also being explored/developed. Telephone genetic counselling has been successfully used for triaging women from high-risk families for TC10 and disclosure of test result 9 30 31. Three RCTs compared telephone counselling to TC in high-risk women attending genetics clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, anxious participants may have difficulty attending to and comprehending information presented over the telephone. Further, genetic counselors may be more attuned to anxiety or other distress cues during an in-person session; thus, they may have greater opportunity to recognize anxiety and appropriately intervene during in-person counseling (Shanley et al, 2007). We will also evaluate the possibility that telephone counseling may be more effective among participants with high levels of decisional conflict.…”
Section: Discussionmentioning
confidence: 99%
“…Shanley et al (2007) reported on their experience with 612 TGC consults through the Royal Marsden NHS Foundation Trust. Sessions were delivered in a timely, convenient manner for patients.…”
mentioning
confidence: 99%